2009
DOI: 10.1093/jpepsy/jsp053
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Don’t Kiss a Sleeping Dog: The First Assessment of “The Blue Dog” Bite Prevention Program

Abstract: Children learned successfully about safe behavior with dogs; thus, the CD can help educate children about dog-bite prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 20 publications
5
66
0
2
Order By: Relevance
“…We assume that by using a panoramic head-camera we can improve these success rates. However, in another study (Meints & Keuster, 2009) it was also found that similarly to our results, participants (in that case children), intermixed the canine emotional expressions of joy and anger. Recent results about autistic children's recognition of robot emotions show that while in case of some emotions (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…We assume that by using a panoramic head-camera we can improve these success rates. However, in another study (Meints & Keuster, 2009) it was also found that similarly to our results, participants (in that case children), intermixed the canine emotional expressions of joy and anger. Recent results about autistic children's recognition of robot emotions show that while in case of some emotions (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Programmes designed for use by children primarily covered pedestrian safety,24 25 30 32 34–36 38–40 fire safety24 29 37 or dog-bite prevention27 28 33 and included seven software programmes,24–31 two internet programmes,32 33 and five programmes using virtual-reality settings 34–40. All four kiosk programmes42–47 targeted parents of young children in clinical settings and covered multiple injury topics (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The most recent study evaluated a CD-based resource featuring cartoon characters designed to engage children and parents in learning about dog safety outside a classroom context (Meints & Keuster, 2009). Unlike the other studies (but consistent with ours), it began by establishing a baseline of children's untrained reactions to depicted scenarios.…”
Section: Educational Interventionsmentioning
confidence: 85%
“…Digital technologies and the internet have recently begun to be used in the delivery of dog safety education. The American Veterinary Medical Association has produced the 'Blue Dog' CD rom with parent guide and has a set of short videos accessible from its website (Meints & Keuster, 2009).…”
Section: Educational Interventionsmentioning
confidence: 99%